Micro Insurance Academy : Improving Health Insurance Coverage in India - Ertekin, Ergun; Navarrete Moreno, Cristina (World Bank, Washington, DC, 2017)
In India, healthcare financing largely relies on direct out-of-pocket spending, which causes immense health-related financial burdens for the poor. Despite recent efforts by the government and the private sector, only 15 percent of the population in India is covered by health insurance. The Micro Insurance Academy (MIA) extends health insurance at the last mile through a bottom-up approach to the design, implementation and management of community-based health insurance. MIA develops an understanding of each community and delivers customized tools and frameworks that build a community’s capacity to self-manage micro insurance schemes. MIA bridges the gap between insurers and the bottom of the pyramid by providing advisory support and insurance education to establish insurance schemes. To date, MIA-supported micro insurance schemes cover more than 40,000 people in India and Nepal.